Self-Acceptance of Adolescent Latino Students with Disabilities - Diane Rodríguez; Kenneth J Luterbach; Sara B Woolf; Sabino Peralta Rivera (Educational Considerations, 2020)
This study examines the relationship of 165 adolescent students who self-identity as Latino and have been identified as having a disability. The participants completed the Perceived Stigma in People with Disabilities (PSPID) and Short Acculturation Scale for Hispanics (SASH) questionnaires to examine factors that may affect the academic engagement of adolescent Latino students with disabilities. The researchers investigated self-acceptance as a factor that may positively predict the academic engagement of adolescent Latino students with disabilities
Keywords: Adolescent; Latino; Learning Disabilities